Modus Pemanfaatan Koperasi dalam Tindak Pidana Pencucian Uang - Beby Suryani Fithri; Windy Sri Wahyuni; Arie Kartika (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
The cooperative's utilization mode is intended to disguise or obscure the proceeds of crime in the crime of money laundering. Money laundering through cooperatives is another criminal act that has been accommodated as an initial crime in law number 8 of 2010. Normative legal research with secondary legal sources and qualitatively analyzed is the research method used in this paper. The impact of money laundering mainly has an impact on the collapse of the community's economy and slows down the pace of national economic growth. The mode of use of cooperatives for money laundering is an iceberg phenomenon that must be handled seriously through strengthening related policies and community participation.